The enlightened economy : Britain and the industrial revolution 1700-1850 - Mokyr, Joel, 1946- (Penguin Books, 2011)
Why did Western countries become so much wealthier than the rest of the world? What explains the huge rise in incomes during the Industrial Revolution - and why did Britain lead the way? In the years between the Glorious Revolution and the Great Exhibition, the British economy was transformed. Joel Mokyr's landmark history offers a wholly new perspective for understanding Britain's extraordinary rise during the Industrial Revolution, showing how intellectual, rather than material, forces were the driving force behind it. While empire, trade, resources and other factors all played a part, above all it was the creative ferment of the Enlightenment - with its belief in progress and scientific advancement - that affected the economic behaviour of thinkers, inventors, entrepreneurs and artisans, taking Britain into the modern era. Linking ideas and beliefs to the heart of modern economic growth, The Enlightened Economy will transform the way we view the Industrial Revolution.